Factors associated with early girl-child pregnancies in Chidamoyo and Magunje areas of Hurungwe District: Zimbabwe - Nyembesi, Samuriwo; Miriam, Chitura; Sungano, Prof Mharakurwa; Auxillia, Prof Chideme Munodawafa (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Early girl-child pregnancy occurring in young girls 13-17 years remains a serious health and socialproblem worldwide and has been associated with many risk factors in the young peoples, family,school and neighbourhoods This study was done to assess factors associated with early girl-childpregnancies in Chidamoyo and Magunje areas of Hurungwe, Zimbabwe, using a case control studydesign to identify factors that may contribute to early girl-child pregnancies, by comparing subjectswho have the early girl-child pregnancy (cases) with subjects who do not have the early girl-childpregnancies, but have their first pregnancies at mature age, but are similar in the fact they are allpregnant women with their first pregnancies. Data were collected from 82 respondents, 4 midwives askey informants and Chidamoyo and Magujne Hospitals Maternity registers. Results showed thatindependent factors associated with early girl-child pregnancies were a) religion, being of apostolicfaith (OR3.34 95%CI 1.35 8.27) were significant religious risk factors associated with early girl-childpregnancies. Low socio-economic status (OR 3.34 95% CI1.35-8.27) was also found to be a risk factorassociated with early girl- child pregnancies. It was conclusion of the study was that being of apostolicreligion, having financial problems and attending school away from home were risk factors associatedwith early girl-child pregnancies in Chidamoyo and Magunje areas of Hurungwe. Communityawareness should be priority in Chidamoyo and Magunje areas of Hurungwe. So the identified multiplefactors contributing to this problem can be used in formulating strategies to address the problem.